Kewirausahaan Sebagai Solusi Pemberdayaan Ekonomi Masyarakat di Desa Dolok Kahean (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) from the University of Muhammadiyah North Sumatra in 2025 took place in Dolok Kahean Village, Tapian Dolok District, Simalungun Regency, with the theme